A Kindred with Familial Cold Urticaria: Linkage Analysis. Issue 1 (March 1974) - Doeglas, H. M. G.; Bernini, L. F.; Fraser, G. R.; Loghem, Erna Van; Khan, P. Meera; Nyenhuis, L. E.; Pearson, P. L.
Abstract : Familial cold urticaria is an autosomal dominant hereditary disease of which seven pedigrees have been published, six from the USA and the present one from Holland. Onset is shortly after birth. The patients develop skin symptoms sometimes accompanied by fever, chills, joint symptoms, and oedema, approximately one half to three hours after generalized exposure to cold. In this paper the linkage data from the Dutch family are described; three generations containing 11 affected persons were studied in relation to 31 markers. While the data are inconclusive, they are presented here from the point of view of eventual accumulation when other families are studied in the same way.